Self-management interventions to reduce healthcare use and improve quality of life among patients with asthma: systematic review and network meta-analysis. (18th August 2020) - Hodkinson, Alexander; Bower, Peter; Grigoroglou, Christos; Zghebi, Salwa S; Pinnock, Hilary; Kontopantelis, Evangelos; Panagioti, Maria
Abstract: Objective: To compare the different self-management models (multidisciplinary case management, regularly supported self-management, and minimally supported self-management) and self-monitoring models against usual care and education to determine which are most effective at reducing healthcare use and improving quality of life in asthma. Design: Systematic review and network meta-analysis. Data sources: Medline, the Cochrane Library, CINAHL, EconLit, Embase, Health Economics Evaluations Database, NHS Economic Evaluation Database, PsycINFO, and ClinicalTrials.gov from January 2000 to April 2019. Review methods: Randomised controlled trials involving the different self-management models for asthma were included. The primary outcomes were healthcare use (hospital admission or emergency visit) and quality of life. Summary standardised mean differences (SMDs) and 95% credible intervals were estimated using bayesian network meta-analysis with random effects. Heterogeneity and publication bias were assessed. Results: From 1178 citations, 105 trials comprising 27 767 participants were included. In terms of healthcare use, both multidisciplinary case management (SMD –0.18, 95% credible interval −0.32 to −0.05) and regularly supported self-management (–0.30, −0.46 to −0.15) were significantly better than usual care. For quality of life, only regularly supported self-management (SMD 0.54, 0.11 to 0.96) showed a statistically significant benefit compared with usual care. For trials including adolescents/children (age 5-18 years), only regularly supported self-management showed statistically significant benefits (healthcare use: SMD –0.21, −0.40 to −0.03; quality of life: 0.23, 0.03 to 0.48). Multidisciplinary case management (SMD –0.32, −0.50 to −0.16) and regularly supported self-management (–0.32, −0.53 to −0.11) were most effective at reducing healthcare use in patients with symptoms of severe asthma at baseline. Conclusions: This network meta-analysis indicates that regularly supported self-management reduces the use of healthcare resources and improves quality of life across all levels of asthma severity. Future healthcare investments should provide support that offer reviews totalling at least two hours to establish self-management skills, reserving multidisciplinary case management for patients with complex disease. Systematic review registration: PROSPERO number CRD42019121350.